Lung injuries associated with electronic cigarette use: an integrative review (Research, Society and Development, 2023)
Objective: to query data on lung injuries associated with e-cigarette use. Methodology: constitutes an integrative literature review in which articles published from 2017 to 2022 were analyzed on the platforms LILACS (Latin American and Caribbean Literature in Health Sciences) and PubMed with the following descriptors “Lung injury”, “vaping” and “acute lung injury". Free articles available on the platforms published in the aforementioned period in English and Portuguese were read. In addition, articles that were dissonant with the descriptors were excluded, as well studies that were not free and those that were published outside the target date. Results: 118 studies were requested based on the descriptors, however, after applying the inclusion and exclusion criteria, only 9 articles were selected to compose the body of the present study and, then, subjected to a thorough analysis for responsible and impartial extraction of information. Conclusion: based on the texts examined, there is a clear relationship between the inhalation of vaporized substances and lung lesions and structural alterations that are capable of leading to a characteristic symptomatological condition, which may progress to the need for mechanical ventilation and death.